Cognitive emotional regulation, social support, and physical activity as predictors of psychological well-being among graduate students at a Malaysian public university - Panahi, Soheila (2014)
The aim of the present study was to investigate the contribution of cognitive emotion regulation, social support, and physical activity on psychological well-being of Malaysian graduate students. For this purpose, 534 graduate students of one Malaysian university were recruited for the study. In determining the samples, proportional sampling was applied to selected samples from six faculties; namely Agriculture, Science, Engineering, Modern Languages, Educational Studies and Medicine. Data were gathered and analysed using descriptive and inferential statistics. The respondents were asked to answer four sets of questionnaires on psychological well-being (autonomy, environmental mastery, personal growth, positive relationship with others, purpose in life, and self-acceptance), cognitive emotion regulation (self-blame, other-blame, rumination, catastrophysing, putting into perspective, positive refocusing, positive reappraisal, planning and acceptance), perceived social support (family, friends, and significant others), and physical activity (three levels of vigorous, moderate, and walking). In this study, the independent variables were cognitive emotion regulation, social support, and physical activity, while the dependent variable was psychological well-being. The results of the present study revealed that the level of psychological well-being mostly used by graduate students was personal growth. As for cognitive emotion regulation the findings demonstrated that the students scored the highest in the strategy, positive reappraisal. As for social support, the respondents depended more on their significant others rather than family and friends. Eight demographic variables (faculty, age, race, number of semesters of study, gender, marital status, employment status, and family size) were also examined in this study. The findings of this quantitative study displayed significant differences in the psychological well-being, particularly in terms of the different faculties, ages, semesters of study, gender, marital and employment status of the respondents. Similarly, significant differences were also found in cognitive emotion regulation of respondents of different faculties, age groups, races, and genders. Social support was also found to be different for respondents in different faculties, age groups, races, genders, and marital status. Moreover, the study showed that the respondents of different faculties, and gender were significantly different in their physical activities. Meanwhile, Pearson correlation analysis confirmed positive relationships between psychological well-being and its components including personal growth, purpose in life, autonomy and age among the graduate students. The findings support that planning is the most influential variable on psychological well-being. Besides, factors such as catastrophysing, significant others, other-blame, reappraisal, self-blame, friend’s support, acceptance, putting into perspective, and walking activity influence graduate students’ psychological well-being. The study concluded that independent variables including cognitive emotion regulation, perceived social support, and physical activity contributed to the dependent variable; psychological well-being. The study supported the previous theories by indicating the relationship between independent (cognitive emotion regulation, perceived social support, and physical activity) and dependent (psychological well-being) variables as mentioned above.